Age-Sex Related in Hematological Values of Sandalwood Pony Horses (Equus caballus) in East Sumba, NTT - Gaina, Cynthia Dewi; Widi, Antin Y. N.; Saputra, Agus (Journal of Veterinary and Animal Sciences; Vol 3 No 2 (2020)DO - 10.24843/JVAS.2020.v03.i02.p06, 2020)
Normal hematological values need to be defined for each category of horse, like age and sex to obtain precise diagnostic results. No published data on hematology exist for Sandalwood horses that are extensively reared in East Sumba, NTT. The main objective of this research was to compare the hematological characteristic of horse group based on age and sex. Blood samples from sixteen horses were collected based on sex into male (n=6), female (n=10) and age groups of 2-3 years (n=4) and 6-10 years old (n=12). About 3 ml of blood sample was collected aseptically from jugular vein of each of these animals in sterile vacutainer tube. The following variables were measured: erythrocyte, leucocyte, platelet, hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and mean platelet volume (MPV). These hematological parameters were calculated with the automatic hematology analyzer at Health Laboratory in Kupang, NTT. This result was analyzed by using student T-test and analysis of variance. These results would contribute to better understanding of the hematological indicators for estimating the physiological status of Sandalwood horse in East Sumba as it can be used as valuable information of its health physiological status.